93 Loss of insurability: an inadequately elucidated harm of screening and overdiagnosis. (20th August 2018) - Dickinson, James; Webb, John
Abstract : Life Insurance assists people to participate in modern society: it is often used to provide security for debts such as mortgages and business overheads, as well as for families in the event of major illness or death. After a serious diagnosis is made, it is well known that health insurance may be unobtainable: it is less known that life insurance also may be either unobtainable or prohibitively priced. We have anecdotal experience of patients who have been harmed through being unable to obtain insurance for home mortgages, after medically trivial diagnoses such as abnormal cervical smear tests. Therfore we sought to understand the process of underwriting and how risks are assessed. We found limited public discussion of the effect of positive screening tests on insurabilty, but higher cost, postponement of contracts, or refusal are consequences. Physicians and the public need to be aware that this is a harm of screning, and therfore insurance should be obtained before undertaking screening for disease. Objectives: We sought to understand the process of underwriting life insurance and assessing risks, particularly about how positive screening tests and their follow-up might affect insurabilty and premium costs. Method: We searched for evidence of company policies about how risks are assessed and the thresholds used to decide to increase the cost of policies, or decide not to insure a proposal. We also searched the insurance business journals for articles discussing this issue. Results: Only limited information is available because much is regarded as commercial in-confidence. We found one article that explicitly described reduced life insurance eligibility as a potential harm of cancer screening. We focussed on cancer screening results and their implications. Some companies have rigid rules, such that almost any cancer diagnosis will not be accepted. Others will postpone acceptance for varied lengths of time. Some have nuanced understanding of the limited risk after diagnosis of cervical pre-cancers, and papillary thyroid cancers. However, since overdiagnosis that occurs in many cancers is indistinguishable from fatal disease, it is largely treated the same. Conclusions: The implication is that people should be warned that having a positive screening test may cause inappropriate loss of insurability, so that they should be sure to obtain any needed life insurance before having such tests. Physicians need to be aware of this hazard to financial health caused by well-meaning screening.